2021
DOI: 10.15252/emmm.202115098
|View full text |Cite
|
Sign up to set email alerts
|

P‐tau235: a novel biomarker for staging preclinical Alzheimer’s disease

Abstract: Alzheimer's disease (AD) is characterised by a long preclinical phase. Although phosphorylated tau (p-tau) species such as p-tau217 and p-tau231 provide accurate detection of early pathological changes, other biomarkers capable of staging disease progression during preclinical AD are still needed. Combining exploratory and targeted mass spectrometry methods in neuropathologically confirmed brain tissue, we observed that p-tau235 is a prominent feature of AD pathology. In addition, p-tau235 seemed to be precede… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 59 publications
1
34
0
Order By: Relevance
“…Tau phosphopeptides pS191, pT217, pT231, pS262, pS262/T263, and pS289 showed a significant increase in AD compared with control samples [31]. Using an exploratory IP-MS approach, tau phosphorylation on brain soluble fraction was shown to reflect CSF, with pT181, pT217, and pT231 among the most prominent species identified in AD [110]. A doubly-phosphorylated tryptic peptide (pT231 + pS235) specific of AD brain was identified in higher amounts than the monophosphorylated (pT231) counterpart [110].…”
Section: Tau Proteinmentioning
confidence: 95%
See 1 more Smart Citation
“…Tau phosphopeptides pS191, pT217, pT231, pS262, pS262/T263, and pS289 showed a significant increase in AD compared with control samples [31]. Using an exploratory IP-MS approach, tau phosphorylation on brain soluble fraction was shown to reflect CSF, with pT181, pT217, and pT231 among the most prominent species identified in AD [110]. A doubly-phosphorylated tryptic peptide (pT231 + pS235) specific of AD brain was identified in higher amounts than the monophosphorylated (pT231) counterpart [110].…”
Section: Tau Proteinmentioning
confidence: 95%
“…Using an exploratory IP-MS approach, tau phosphorylation on brain soluble fraction was shown to reflect CSF, with pT181, pT217, and pT231 among the most prominent species identified in AD [110]. A doubly-phosphorylated tryptic peptide (pT231 + pS235) specific of AD brain was identified in higher amounts than the monophosphorylated (pT231) counterpart [110]. Using sarkosyl-insoluble samples, Wesseling et al [70] performed a quantitative and qualitative tau protein profiling (FLEXITau and Q-Exactive MS) of 29 AD patients and 28 matched control individuals.…”
Section: Tau Proteinmentioning
confidence: 99%
“…Accumulating studies have revealed an initial role of hTau pathologies in neurodegenerative disease 8,9 . In P301S mutation cases, the mean age of clinical onset and death was reported as early as ∼34.3 and ∼40.8‐year old, respectively 10 .…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7] Accumulating studies have revealed an initial role of hTau pathologies in neurodegenerative disease. 8,9 In P301S mutation cases, the mean age of clinical onset and death was reported as early as ∼34.3 and ∼40.8-year old, respectively. 10 As clinical symptoms developed, the temporal atrophy rate was detectably increased in P301Scarried patients, followed by atrophy of the parietal and frontal lobes.…”
Section: Introductionmentioning
confidence: 99%
“… 6 Another p-tau epitope, CSF p-tau235, is significantly increased at the later phase of preclinical Alzheimer. 7 It needs to be investigated to what extent each of the p-tau epitopes provide different information on the disease and what they may be more useful for, both in clinical practice and in research settings.…”
mentioning
confidence: 99%